Regulation of adiponectin production by insulin: interactions with tumor necrosis factor-α and interleukin-6 - Hajri, Tahar (American Physiological Society, 2011)
Obesity is often associated with insulin resistance, low-grade systemic inflammation, and reduced plasma adiponectin. Inflammation is also increased in adipose tissue, but it is not clear whether the reductions of adiponectin levels are related to dysregulation of insulin activity and/or increased proinflammatory mediators. In this study, we investigated the interactions of insulin, tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6) in the regulation of adiponectin production using in vivo and in vitro approaches. Plasma adiponectin and parameters of insulin resistance and inflammation were assessed in a cohort of lean and obese insulin-resistant subjects. In addition, the effect of insulin was examined in vivo using the hyperinsulinemic-euglycemic clamp, and in adipose tissue (AT) cultures. Compared with lean subjects, the levels of total adiponectin, and especially the high-molecular-weight (HMW) isomer, were abnormally low in obese insulin-resistant subjects. The hyperinsulinemic clamp data confirmed the insulin-resistant state in the obese patients and showed that insulin infusion significantly increased the plasma adiponectin in lean but not obese subjects (P < 0.01). Similarly, insulin increased total adiponectin release from AT explants of lean and not obese subjects. Moreover, expression and secretion of TNF-α and IL-6 increased significantly in AT of obese subjects and were negatively associated with expression and secretion of adiponectin. In 3T3-L1 and human adipocyte cultures, insulin strongly enhanced adiponectin expression (2-fold) and secretion (3-fold). TNF-α, and not IL-6, strongly opposed the stimulatory effects of insulin. Intriguingly, the inhibitory effect of TNF-α was especially directed toward the HMW isomer of adiponectin. In conclusion, these studies show that insulin upregulates adiponectin expression and release, and that TNF-α opposes the stimulatory effects of insulin. A combination of insulin resistance and increased TNF-α production could explain the decline of adiponectin levels and alterations of isomer composition in plasma of obese insulin-resistant subjects.